Parental background matters intergenerational mobility and assimilation of Italian immigrants in Germany - Bönke, Timm; Neidhöfer, Guido (Freie Univ. Berlin, FB Wirtschaftswiss., 2014)
We investigate the hypothesis of failed integration and low social mobility of immigrants. For this purpose, an intergenerational assimilation model is tested empirically on household survey data and validated against administrative data provided by the Italian Embassy in Germany. In line with previous studies, we confirm substantial inequality of educational achievements between immigrants and natives. However, we find that the children of Italian immigrants exhibit fairly high intergenerational mobility. Furthermore, holding parental education constant, Italian second generation immigrants show no less opportunities than natives to achieve high schooling degrees. These findings suggest a rejection of the failed integration hypothesis.
Keywords: Generation 2; Ungleichheit; Italiener; Bildung; Intergenerationenmobilität; Deutschland